Media Sosial, Word Of Mouth Dan Physical Environment Terhadap Proses Keputusan Pembelian - Debby Suryana (Jurnal Bisnis dan Manajemen, 2021)
The purpose of this research are to analyze the influence of social media, word of mouth and physical environment on purchasing decision processes, and to analyze the dominant variables between social media, word of mouth, and physical environment for the purchasing decision process. The number of respondents in this study is 138 people. The data obtained analyzed using multiple linear regression analysis. The results showed that social media, word of mouth and physical environment had a significant effect on the purchasing decision process. Based on the results of multiple regression analysis, it can be seen that the largest regression coefficient value is the physical environment, this means that the physical environment is a variable that has a dominant influence on the purchasing decision process, followed by word of mouth and social media variables.